Economically and thermodynamically efficient heat pump-assisted side-stream pressure-swing distillation arrangement for separating a maximum-boiling azeotrope. (5th June 2020) - Zhang, Qingjun; Yang, Shunjin; Shi, Pengyuan; Hou, Wei; Zeng, Aiwu; Ma, Youguang; Yuan, Xigang
Graphical abstract: (a) VRC-SSPSD-PF-HEN; (b) VAB-SSPSD-PF-HEN. Highlights: Two novel improved heat pump-assisted side-stream pressure-swing distillation options are investigated. The recommended arrangement can achieve reduction of 30.23% in TAC compared to the basic case. The multi-stage compression process is used to decrease the higher compressor discharged temperature. Abstract: The feasibility and effectiveness for the two types of heat pump-assisted side-stream pressure-swing distillation arrangements (vapor recompression and bottom flashing heat pump-assisted systems) are investigated with the separation of a maximum-boiling ethylenediamine and water azeotrope as the demonstrating example. To further improve the heat recovery within the process as much as possible and reduce the excessive utilization of cold and hot utilities, the efficient Heat Exchanger Network Synthesis (HENs) analysis tool is adopted. Total annual cost (TAC), carbon footprints and thermodynamic efficiency are as the evaluation indicators to assess and screen the eco-efficient arrangement in a series of pressure-swing distillation (PSD) processes. Compared to the partially heat-integrated PSD process, the economically optimum flowsheet is the intensified self-heat recuperative vapor recompression-assisted arrangement (VRC-SSPSD-PF-HEN) since it can achieve the reductions of 59.01% in energy consumption rates, 86.60% in CO2 emissions, 12.78% in TAC and enhancement of 143.38% in thermodynamic efficiency. And the amount of heat recovery within this process is 7028.0 kW with the requirement of cold utility 395 kW and without any hot utility consumptions (electrical power is required). Besides, the exergy destroyed in each component for the optimal intensified alternative is analyzed. Result shows that the major exergy losses mainly produce in columns, especially in high-pressure column.